Drinking water quality parameters in Africa and the United States: Implications for public health - (:unkn) unknown (My University, 2024)
This study provides a comparative overview of drinking water quality parameters in Africa and the United States, highlighting their implications for public health. Water quality encompasses physical, chemical, biological, and radiological characteristics, with significant variations influenced by source conditions and treatment processes. In Africa, inadequate infrastructure, pollution, and limited resources result in high levels of microbiological contaminants and chemical pollutants, leading to a high burden of waterborne diseases. Pathogens such as Escherichia coli and protozoan parasites like Cryptosporidium and Giardia are prevalent, contributing to substantial morbidity and mortality. Chemical contamination, including nitrates, pesticides, and heavy metals, exacerbates these issues. Conversely, the United States benefits from advanced water treatment technologies and stringent regulations, yet challenges persist. Issues such as lead contamination from aging pipes, emerging pollutants like PFAS, and localized contamination events continue to pose risks. Although regulatory frameworks like the Safe Drinking Water Act and proposed enhancements to the Lead and Copper Rule aim to mitigate these problems, maintaining and upgrading
Keywords: African Research